Beispiel Nr: 06
$ \text{Gegeben:} \\ a1 \cdot x + b1\cdot y + c1\cdot z=d1\\ a2\cdot x + b2\cdot y + c2\cdot z=d2\\ a3\cdot x + b3\cdot y + c3\cdot z=d3\\ \\ \text{Gesucht:} \\\text{x,y,z} \\ \\ \textbf{Gegeben:} \\ -2 x -8 + 0 z=1\\ 1 x +4 y + 0 z=-\frac{1}{2}\\ 8 x -2 y + -1 z=8\\ \\ \\ \textbf{Rechnung:} \\ -2 x + -8 y + 0 z=1\\ 1 x +4 y +0 z=-\frac{1}{2}\\ 8 x -2 y -1 z=8\\ D_h=\left|\begin{array}{ccc} -2\ & -8 & 0\\ 1&4 & 0\\ 8& -2 & -1 \\ \end{array}\right| \begin{array}{cc} -2\ & -8 \\ 1&4 \\ 8& -2 \end{array} \\ D_h=\left(-2\right) \cdot 4 \cdot \left(-1\right)+\left(-8\right) \cdot 0 \cdot 8 +0 \cdot 1 \cdot \left(-2\right) - 0 \cdot 4 \cdot 8 -\left(-2\right) \cdot 0 \cdot \left(-2\right) -\left(-8\right) \cdot 1 \cdot \left(-1\right)=0 \\ D_x=\left|\begin{array}{ccc} 1\ & -8 & 0\\ -\frac{1}{2}&4 & 0\\ 8& -2 & -1 \\ \end{array}\right| \begin{array}{cc} 1\ & -8 \\ -\frac{1}{2}&4 \\ 8& -2 \end{array} \\ D_x=1 \cdot 4 \cdot \left(-1\right)+ \left(-8\right) \cdot 0 \cdot 8 +0 \cdot \left(-\frac{1}{2}\right) \cdot \left(-2\right) - 0 \cdot 4 \cdot 8 - 1 \cdot 0 \cdot \left(-2\right) -\left(-8\right) \cdot \left(-\frac{1}{2}\right) \cdot \left(-1\right)=0\\ D_y=\left|\begin{array}{ccc} -2\ & 1 & 0\\ 1&-\frac{1}{2} & 0\\ 8& 8 & -1 \\ \end{array}\right| \begin{array}{cc} -2\ & 1 \\ 1&-\frac{1}{2} \\ 8& 8 \end{array} \\ D_y=\left(-2\right) \cdot \left(-\frac{1}{2}\right) \cdot \left(-1\right)+1 \cdot 0 \cdot 8 +0 \cdot 1 \cdot 8 - 0 \cdot \left(-\frac{1}{2}\right) \cdot 8 -\left(-2\right) \cdot 0 \cdot 8 -1 \cdot 1 \cdot \left(-1\right)=0 \\ D_z=\left|\begin{array}{ccc} -2\ & -8 & 1\\ 1&4 & -\frac{1}{2}\\ 8& -2 & 8 \\ \end{array}\right| \begin{array}{cc} -2\ & -8 \\ 1&4 \\ 8& -2 \end{array} \\ D_z=\left(-2\right) \cdot 4 \cdot 8+\left(-8\right) \cdot \left(-\frac{1}{2}\right) \cdot 8 +1 \cdot 1 \cdot \left(-2\right) - 1 \cdot 4 \cdot 8 -\left(-2\right) \cdot \left(-\frac{1}{2}\right) \cdot \left(-2\right) -\left(-8\right) \cdot 1 \cdot 8=0\\ \\ L= unendlich$